DIGITAL TOOLS AND STUDENTS’ SPEAKING SKILL - Fitriani Fitriani (VISION, 2020)
Teaching speaking to EFL learners is tremendouslychallenging. Having learned English for years at school andacquired sufficient vocabulary and grammatical features,students remain struggling to speak English effortlessly. Forthat matter, employing digital tools in teaching speaking canbe regarded as a prospective solution since some of which areparticularly designed for English language learning. Thesetools equip teachers with unlimited and up-to-date resourcesas well as facilitate students to be a lot more involved in thelearning activities and are expected to better perform theirspeaking ability. Accordingly, researcher utilized some digitaltools to teach students speaking skill to figure out the impacton their learning growth. This research employed quantitativeapproach to portray in detail the statistic descriptive ofstudents’ scores which reflects students’ speaking proficiencyprogress and their perspective and attitude regarding theelectronic devices use. From this data, further, it could beconsidered the benefits, disadvantages and follow up steps toescalate the potential application of such tools in teachingspeaking.